Examining ventral subiculum and basolateral amygdala projections to the nucleus accumbens shell: Differential expression of VGLuT1, VGLuT2 and VGaT in the rat. (25th September 2022) - Jin, Shubo; Maddern, Xavier J.; Campbell, Erin J.; Lawrence, Andrew J.
Highlights: The accumbens shell receives dense VGluT1 input from the ventral subiculum. Almost 25% of subiculum to accumbens projections co-expressed VGluT1 and VGluT2. The accumbens shell also receives dense VGluT1 input from the basolateral amygdala. Only ∼3 % of amygdala to accumbens projections co-expressed VGluT1 and VGluT2. Instead, almost a quarter of amygdala to accumbens projections expressed VGaT. Abstract: Projections to the striatum are well-identified. For example, in the ventral striatum, two major inputs to the medial nucleus accumbens shell include the ventral subiculum and basolateral amygdala. However, the chemical phenotype(s) of these projection neurons remain unclear. In this study, we examined amygdalostriatal and corticostriatal connectivity in rats using injections of the retrograde tracer cholera toxin b into the nucleus accumbens shell. To determine the neurotransmitter identity of projection neurons, we combined retrograde tracing with RNAscope in-situ hybridization, using mRNA probes against vesicular transporters associated with glutamatergic (VGluT1 – Slc17a7, VGluT2 – Slc17a6 ) or GABAergic (VGaT – Slc32a1 ) neurotransmission. Confocal imaging was used to examine vesicular transporter mRNA expression in the ventral subiculum and basolateral amygdala inputs to the nucleus accumbens shell. Both projections contained mostly VGluT1-expressing neurons. Interestingly, almost a quarter of ventral subiculum to nucleus accumbens shell projections co-expressed VGluT1 and VGluT2 compared to a relatively small number (∼3%) that were co-expressed in basolateral amygdala to nucleus accumbens shell afferents. However, almost a quarter of basolateral amygdala to nucleus accumbens shell projections were VGaT-positive. These findings highlight the diverse proportions of glutamatergic and GABAergic afferents in two major projections to the nucleus accumbens shell and raise important questions for functional studies.